The characterization of the sandwich composite consisted of coconut fibre-polyester resin and its variations of wood core / Sumarji … [et al.] - -, Sumarji; -, Wazirotus Sakinah; Widityo, R. Puranggo Ganjar; Asrofi, Mochamad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The traditional fishing vessels in Indonesia are usually made of wood material. The weakness of this vessel material is that it is easily weathered when exposed to seawater. For this reason, it is necessary to have vessel material engineering from composite sandwiches. This study aimed to prepare and investigate the flexural test, impact test, optical microscopy (OM), and scanning electron microscopy (SEM) observations of sandwich composites based on coconut fibre-polyester resin and wood core. The fabrication uses a hand lay-up method with a constant volume fraction (20% coconut coir fibre) and wood core variations type. The primary wood variations used are albizia chinensis, mahogany, shorea, and camphor. The Surface modification of fibre and wood core was conditioned without treatment and with treatment with about 5% NaOH solution for 2 hours. The study showed that the highest bending and impact strength was sandwich composite with camphor wood cores with alkali treatment for 39.75 MPa and 37.22 J/cm2, respectively. The OM observations showed that the core and skin interface area failed to delaminate after flexural and impact tests.